Advanced Flame Retardant Materials - Laoutid, Fouad (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Recent disasters caused by the spread of fire in buildings and in transportations remind us of the importance of fire protection. Using flame-retardant materials is one important element of the firefighting strategy, which aims to prevent fire development and propagation. These materials are used in different applications, such as in textiles, coatings, foams, furniture, and cables. The development of more efficient and environmentally friendly flame-retardant additives is an active multidisciplinary approach that has attracted a great deal of interest. Studies have aimed at the development of new, sustainable, and flame-retardant additives/materials, providing high performance and low toxicity. Also studied were their properties during ageing and recycling, as well as modeling physical and chemical processes occuring before ignition and during their combustion. The development of sustainable flame retardants and understanding their modes of action provide a strong link between these topics and cover many fields from organic chemistry, materials engineering, and toxicology, to physics and mathematics.